2017
DOI: 10.14814/phy2.13103
|View full text |Cite
|
Sign up to set email alerts
|

Chronic TrkB agonist treatment in old age does not mitigate diaphragm neuromuscular dysfunction

Abstract: Previously, we found that brain‐derived neurotrophic factor (BDNF) signaling through the high‐affinity tropomyosin‐related kinase receptor subtype B (TrkB) enhances neuromuscular transmission in the diaphragm muscle. However, there is an age‐related loss of this effect of BDNF/TrkB signaling that may contribute to diaphragm muscle sarcopenia (atrophy and force loss). We hypothesized that chronic treatment with 7,8‐dihydroxyflavone (7,8‐DHF), a small molecule BDNF analog and TrkB agonist, will mitigate age‐rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…During aging, the availability of TrkB receptors appears to decline in DIAm motor units (Greising et al. 2015b, ), although fiber‐type‐specific effects are currently unknown. Inhibiting TrkB signaling in young adult rodents results in neuromuscular transmission failure and neuromuscular junction defects at type IIx and/or IIb fibers (Mantilla et al.…”
Section: Discussionmentioning
confidence: 99%
“…During aging, the availability of TrkB receptors appears to decline in DIAm motor units (Greising et al. 2015b, ), although fiber‐type‐specific effects are currently unknown. Inhibiting TrkB signaling in young adult rodents results in neuromuscular transmission failure and neuromuscular junction defects at type IIx and/or IIb fibers (Mantilla et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that DIAm sarcopenia is associated with a loss of motor neurons and fiber type‐selective atrophy (Greising, Mantilla, et al, ; Greising, Medina‐Martínez, et al, ; Khurram et al, ; Mantilla & Sieck, ), dysfunction at the neuromuscular junction (Fogarty, Gonzalez Porras, Mantilla, & Sieck, ; Greising, Stowe, Sieck, & Mantilla, ; Holter, Kierulf, & Refsum, ; Mantilla & Sieck, ), or intrinsic muscle changes including mitochondrial degeneration and autophagy (Gonzalez Porras, ). For instance, from 6 to 24 mo in C57BL/6 male and female mice, there is fiber type‐selective atrophy of large, high force generating type IIx and/or IIb fibers (Elliott, Omar, Mantilla, & Sieck, ; Greising, Mantilla, et al, , ; Greising, Medina‐Martínez, et al, ; Greising, Vasdev, Zhan, Sieck, & Mantilla, ). However, a recent study found significant DIAm hypertrophy of type IIx fibers (~30% increase in fiber cross‐sectional area (CSA)) in female CD‐1 mice at 20 mo compared to 5 mo (Messa et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Larger motor unit potentials may generate larger forces that could be an adaptation to diaphragm muscle fibre atrophy (Greising et al . ), particularly in the stronger type II muscle fibre phenotype (Eddinger et al . ; Gosselin et al .…”
Section: Discussionmentioning
confidence: 99%
“…A larger action potential area in diaphragm motor units of middle-aged and older groups compared to the young group is consistent with age-related changes in the motor unit potentials observed in the genioglossus (Saboisky et al 2014) and vastus lateralis (Piasecki et al 2016) muscles. Larger motor unit potentials may generate larger forces that could be an adaptation to diaphragm muscle fibre atrophy (Greising et al 2017), particularly in the stronger type II muscle fibre phenotype (Eddinger et al 1985;Gosselin et al 1992;Prakash & Sieck, 1998;Imagita et al 2009;Greising et al 2013). A loss of type II fibres in humans is supported by the reduced maximal inspiratory muscle strength in the older participants.…”
Section: Motor Unit Potential Morphologymentioning
confidence: 99%